“Ellipticam” and the Philosophy of Dermatological Surgery of the Head - Gualdi, Giulio; Cattaneo, Isacco; Amerio, Paolo (Dermatology Practical & Conceptual, 2026)
Introduction: Dermatological surgery pursues two primary goals: complete tumor excision and optimal functional and aesthetic outcomes. The standard elliptical excision minimizes dog-ears by aligning sutures with Langer’s lines, but in anatomically and aesthetically sensitive areas (e.g., eyelids, lips, nose), alternative reconstructions are needed.Objectives: To present a Tangram-inspired framework (“Ellipticam”) for the reconstruction of elliptical excisions in challenging anatomical areas, aiming to optimize both closure and aesthetic outcomes.Methods: The Ellipticam method decomposes an elliptical excision into geometric components (triangles and rectangles) and reassembles them as flaps. This approach underlies multiple surgical designs, including single tangent advancement, opposing triangles, east-to-west, cuneiform wedge, split-advancement, rotation flaps, and multiple double-tangent designs.Results: Each flap reuses all subunits of the ellipse and aligns incisions along low-tension lines to facilitate closure. This method allows precise adaptation to the defect while minimizing tissue waste and visible scarring.Conclusions: Understanding the indications, geometric principles, and elastic behavior of these flaps empowers dermatologic surgeons to manage defects in complex head and neck areas with greater confidence and better aesthetic results.